Targeted Diphtheria Toxin-Based Therapy: A Review Article - Shafiee, Fatemeh; Aucoin, Marc G.; Jahanian-Najafabadi, Ali (Frontiers in Microbiology, 2019)
Cancer remains one of the leading causes of death worldwide. Conventional therapeutic strategies usually offer limited specificity resulting in severe side effects and toxicity to normal tissues. Targeted cancer therapy, on the other hand, can improve the therapeutic potential of anti-cancer agents and decrease unwanted side effects. Targeted applications of cytolethal bacterial toxins have been found to be especially useful for the specific eradication of cancer cells. Targeting is either mediated by peptides or protein targeting moieties, such as antibodies, antibody fragments, cell-penetrating peptides, growth factors or cytokines. Together with a toxin domain, these molecules are more commonly referred to as immunotoxins. Targeting can also be achieved through gene delivery and cell-specific expression of a toxin. Of the available cytolethal toxins, diphtheria toxin (DT) is one of the most frequently used for these strategies. Of the many DT-based therapeutic strategies investigated to date, two immunotoxins, Ontak™ and Tagraxofusp™, have gained FDA approval for clinical applications. Despite some success with immunotoxins, suicide gene therapy strategies are gaining prominence, whereby controlled tumor specific expression of DT is used for the eradication of malignant cells. The first part of this review focuses on DT-based immunotoxins, followed by recent developments in tumor specific expression of DT.